KAJIAN TEKNOLOGI DIRECT–PROCESS SINTESA DI–METHYL ETHER(DME) DARI BATUBARA, BIOMASSA DAN GAS ALAM - Bambang Suwondo Rahardjo (Badan Pengkajian dan Penerapan Teknologi, 2011)
Di–Methyl Ether (DME) is the simplest ether compund with chemical formula CH3OCH3or also known as methyl ether or wood ether, whichcan be produced two ways namely direct–process and indirect–process. Direct–process is the process of syngas (H2+CO) formation which can be produced via gasification of coal / biomass or partial oxidation of natural gas,and then synthesized into DME. While the indirect–process is a process that begins with MeOH manufacturing, followed by MeOH dehydration in a separate reactor synthesized into DME. Utilization of energy resources means increased economical value and as an effort to reduce dependence on fosil fuels as well as solves the environmental pollution problems. Until now, most DME is made by indirect–process via the catalytic dehydration of MeOH in the fixed–bed reactor (a simple process and low capital investment) is licensed by Lurgi, Haldor–Topsoe, Mitsubishi Chemical Gas (MGC) and Toyo Engineering Corporation (TEC), while the direct–process technology with the high efficiency proposed by Haldor Topsoe, JFE and Air Products Chemicals Inc. is under development stage in Japan, USA as well as China, and so far not fully yet commercial. This paper will discuss about the technology of DME direct–process synthesis from syngas through coal/biomass gasification or natural gas partial oxidation process as an environmentally friendly alternative fuel. Kata kunci: DME, direct process, batubara, biomasa, gas alam